Osmanlı Devleti’nin Sığır Vebası Mücadelesinde Unutulmuş Bir İsim: Şehremaneti Baytar Müfettişi Mehmed Haydar - Seda TAN (Gazi Akademik Bakış)
Rinderpest is recognized as the most contagious and fatal animal disease in the historical process. The disease, which maintained its effectiveness until the 20th century, has been the subject of socio-economic grievances since the earliest times for the Ottomans, who had a deep-rooted husbandry culture. However, the increase in human and animal mobility with the development of technology greatly increased the number and frequency of attacks in the 19th century. In this contex, it should be noted that the great wars experienced are also important reinforcements. In the face of the epidemics, the Ottoman central authority, albeit belatedly, attempted to establish the civil veterinary medicine organization with the example of its European contemporaries, who represented the modern world. The study focuses on Şehremaneti Veterinary Inspector Mehmet Haydar, who was a very important figure in the establishment of modern civil veterinary medicine culture in the Ottomans. M.Haydar, who was originally a soldier, carried out the civil duty in question for many years due to the very low number of experts in the field, and in this context, he played a key role in the test of the capital against the rinderpest. The study focused on determining his place in the Turkish veterinary medicine organization and revealing his role in the eradication of rinderpest.